GEOCHEMICAL PECULIARITIES OF GROUNDWATER WITHIN THE TERRITORY OF LVIV TROUGH - Паньків, Р. П.; Кость, М. В.; Сахнюк, І. І.; Майкут, О. М.; Мандзя, О. Б.; Навроцька, І. П.; Козак, Р. П. (Water and Water Purification Technologies. Scientific and Technical News, 2014)
In this paper based on the definition of indicators of the chemical composition of the groundwater its ecological status and degree of contamination is appraised. Increased content of nitrates, silicon, alkalinity and high values of the general hardness were fixed. Deviations of physiological full value of the mineral composition of drinking water from guideline values were revealed. It was established that the formation of geochemical composition of ground water was due to the influence of factors of geological, physical, chemical and man-made origin. Recommendations for reduction of pollution of drinking water and improvement its quality were cited.